2010
DOI: 10.1042/cs20100190
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive genotype–phenotype interaction of different Toll-like receptor variations in a renal transplant cohort

Abstract: To date, the impact of the TLR (Toll-like receptor) system on early and late kidney transplantation outcome, such as ARE (acute rejection episodes) or cardiovascular morbidity and mortality, has still not been elucidated conclusively. Genetically determined alterations in TLR expression exhibit a possibility to evaluate their role in transplantation. In the present study, we sought to determine a comprehensive genotype-phenotype association with early and late allograft outcomes. We studied 11 SNPs (single nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 42 publications
1
38
1
Order By: Relevance
“…22 There are increasing data supporting a role of TLRs in inflammatory kidney diseases. 17,23,24 Endocytosed antigens usually enter the MHC class II pathway to permit CD4+ T cell activation. Only professional APCs are able to also pass Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…22 There are increasing data supporting a role of TLRs in inflammatory kidney diseases. 17,23,24 Endocytosed antigens usually enter the MHC class II pathway to permit CD4+ T cell activation. Only professional APCs are able to also pass Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…The SNPs at rs3775291 and rs13126816 in the TLR3 gene were correlated with a reduced incidence of genital HSV-2 infection but did not affect disease severity in the infected hosts [35]. The L412F SNP was not associated with HCMV infection in renal transplant recipients, although it was linked with the incidence of acute rejection and graft function [21]. This polymorphism was also over-represented in other diseases, including liver recipients infected with human hepatitis C virus [46], infants with bronchiolitis [47], and individuals with asthma [40] or Japanese encephalitis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies on the relevance of the TLR2 R753Q polymorphism in a total of >800 liver transplant recipients found a significantly increased risk for severe CMV disease in patients with a mutated genotype [9,10]. Another study evaluated the polymorphism in 265 kidney-transplant patients and found no significant effect in relation to graft survival, renal function, or incidence of opportunistic infections, including CMV infection [11]. We were unable to identify a significant effect of the polymorphism on incidence of tissueinvasive CMV disease or viremia in 175 HTX patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the TLR R753Q polymorphism was not associated with an increased risk for CMV replication and disease in kidney transplant recipients [11]. Moreover, Jablonska et al observed a significantly lower frequency of heterozygosity for the TLR2 R753Q polymorphism in immunocompetent patients with primary CMV infection when compared to non-infected individuals [12].…”
Section: Introductionmentioning
confidence: 93%